Doomsurfing and doomscrolling mediate psychological distress in COVID‐19 lockdown: Implications for awareness of cognitive biases. Issue 1 (20th April 2021) - Anand, Nitin; Sharma, Manoj Kumar; Thakur, Pranjali Chakraborty; Mondal, Ishita; Sahu, Maya; Singh, Priya; J., Ajith S.; Kande, Jayesh Suresh; MS, Neeraj; Singh, Ripudaman
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has led to a significant increase in the consumption of the internet for work, leisure time activities, and has also generated substantial amounts of anxiety, and uncertainty, which has lead individuals to spend a lot of time surfing the internet for the latest news on developments in the COVID‐19 crisis. This ends up as scrolling or surfing through a lot of pessimistic news items. This search for information during COVID‐19 is apparently influenced by a number of cognitive biases as well as mediated by poor affect regulation skills. Thus, there is a need to address these cognitive biases and promote affect regulation strategies across health settings.